2020
DOI: 10.1002/joc.6882
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing wheat yield stability on the North China Plain: Relative contributions from climate change in mean and variability

Abstract: There has been increasing interest in understanding climate change impacts on crop yield stability, including interannual yield variability and lower yield extremes, in addition to mean yield. In this study, we evaluated these impacts on wheat yield and investigated the contribution of changes in climate mean and variability, and their interaction, on the North China Plain (NCP). Wheat yield simulation experiments with control groups were conducted using the Crop Environment Resource Synthesis (CERES) model, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
(84 reference statements)
1
8
0
Order By: Relevance
“…Given that it is one of the primary wheat cropping regions in China, wheat productivity in the North China Plain (NCP) has been declining due to increased extreme weather events (e.g., drought stress and temperature stress) driven by climate change, especially in the southern part [4]. These extreme weather events cause large wheat yield variability in the NCP [5]. With climate change, more cropping regions like NCP will face a greater risk of abiotic stress due to higher frequencies and greater magnitudes of extreme temperature and rainfall events [6].…”
Section: Introductionmentioning
confidence: 99%
“…Given that it is one of the primary wheat cropping regions in China, wheat productivity in the North China Plain (NCP) has been declining due to increased extreme weather events (e.g., drought stress and temperature stress) driven by climate change, especially in the southern part [4]. These extreme weather events cause large wheat yield variability in the NCP [5]. With climate change, more cropping regions like NCP will face a greater risk of abiotic stress due to higher frequencies and greater magnitudes of extreme temperature and rainfall events [6].…”
Section: Introductionmentioning
confidence: 99%
“…These models use climate change scenarios developed from multiple GCMs that account for various climatic considerations. Several studies have used the DSSAT CERES-Wheat model to forecast the effect of changing climate on crop growth and production under different representative concentration pathway (RCP) scenarios [32,33]. It is a CSM that is part of the DSSAT [34,35], which helps to investigate the effects of soil, management of the field (such as fertilizer, irrigation, cultivar, date of planting, and planting density), and climate variability on plant development and yield [32].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have used the DSSAT CERES-Wheat model to forecast the effect of changing climate on crop growth and production under different representative concentration pathway (RCP) scenarios [32,33]. It is a CSM that is part of the DSSAT [34,35], which helps to investigate the effects of soil, management of the field (such as fertilizer, irrigation, cultivar, date of planting, and planting density), and climate variability on plant development and yield [32]. The model considers climate, soil, genetic factors, and management options when predicting wheat growth, water balance, nitrogen balance, aboveground biomass, and grain yield [36].…”
Section: Introductionmentioning
confidence: 99%
“…In the past half-century, the yield of most major crops in the world has increased significantly, mainly due to irrigation, chemical input, and the extensive use of modern crop varieties [8]. However, an increasing number of studies have shown that there are two significant differences between the positive and negative effects of climate warming on crop growth and yield [9][10][11][12][13], and the results depend on the study areas, crops, and methods. In the past 100 years, the trend of temperature increase in China has been higher than the global average [14].…”
Section: Introductionmentioning
confidence: 99%